Efektivitas Feromon terhadap Interest Kumbang Tanduk (Oryctes rhinoceros) pada Tanaman Kelapa (Cocos nucifera L.) - Putri Sri Anggini; Lalu Wahyudi; Feky Recky Mantiri (JURNAL BIOS LOGOS, 2022)
(Article History: Received Mar 1, 2022; Revised Mar 14, 2022; Accepted Apr 11, 2022)The population of Oryctes rhinoceros that out of control at coconut plantation could be effect on productivity. Therefore, necessary to control using pheromone traps. Pheromones as chemical compounds use to reproduction communicate between individual beetles. The purpose of this study was to reveal the potential of synthetic pheromones in order to control the population of horn beetle (O. rhinoceros). This study conducted observation and response of application pheromone to the population of O. rhinoceros and offcourse the leaf counting as parametre of the degree bettles offensive. The analyze quantitative of sample with associated the decrease coconut productivity. The results of this study indicate that pheromone traps was effective to control the O. rhinoceros by the number of beetles trapped at the area coconut plantations in Pineleng Village, there are160 tails and the ratio of male and female beetles was 1:2. Representative in this area was classified high degree offensive where obtained 6-7 beetles/ha and 45% losses of productivity.Keywords: Oryctes rhinoceros L.; pheromones; coconut plant; attack intensity.Abstrak Populasi kumbang Oryctes rhinoceros yang meningkat secara berkepanjangan tanpa adanya pengendalian dapat menyebabkan penurunan produktivitas kelapa dan kerugian bagi masyarakat, hal ini disebabkan oleh serangan dari kumbang Oryctes rhinoceros. Oleh karena itu diperlukan pengendalian salah satunya menggunakan perangkap berferomon. Tujuan penelitian ini adalah untuk mengungkapkan potensi feromon dalam mengendalikan populasi kumbang tanduk (O. rhinoceros). Penelitian ini menggunakan metode observasi dan respons aplikasi feromon untuk memonitoring populasi kumbang O. rhinoceros dan mengetahui intensitas serangan dengan cara menghitung pelepah daun kelapa yang terserang selama dua bulan disetiap minggunya. Kemudian dianalisis secara kuantitatif sederhana dan dihubungkan dengan penurunan produktivitas kelapa. Hasil penelitian menunjukan bahwa penggunaan perangkap berferomon sebagai pengendalian kumbang O. rhinoceros sangat efektif dengan jumlah kumbang yang terperangkap di perkebunan kelapa dalam Desa Pineleng sebanyak 160 ekor dengan perbandingan kumbang jantan dan betina yaitu 1:2. Intensitas serangan kumbang tergolong dalam kategori tinggi mencapai 6-7 ekor/ha dan menyebabkan penurunan produktivitas buah sebesar 45 %.Kata kunci: Oryctes rhinoceros L.; feromon; tanaman kelapa; intensitas serangan.